Prenatal diagnosis of cerebro‐oculo‐facio‐skeletal syndrome: Report of three fetuses and review of the literature. Issue 5 (13th February 2020) - Le Van Quyen, Pauline; Calmels, Nadège; Bonnière, Maryse; Chartier, Suzanne; Razavi, Féréchté; Chelly, Jamel; El Chehadeh, Salima; Baer, Sarah; Boutaud, Lucile; Bacrot, Séverine; Obringer, Cathy; Favre, Romain; et al.
Abstract: Cerebro‐oculo‐facio‐skeletal syndrome (COFS) is a rare autosomal recessive neurodegenerative disease belonging to the family of DNA repair disorders, characterized by microcephaly, congenital cataracts, facial dysmorphism and arthrogryposis. Here, we describe the detailed morphological and microscopic phenotype of three fetuses from two families harboring ERCC5/XPG likely pathogenic variants, and review the five previously reported fetal cases. In addition to the classical features of COFS, the fetuses display thymus hyperplasia, splenomegaly and increased hematopoiesis. Microencephaly is present in the three fetuses with delayed development of the gyri, but normal microscopic anatomy at the supratentorial level. Microscopic anomalies reminiscent of pontocerebellar hypoplasia are present at the infratentorial level. In conclusion, COFS syndrome should be considered in fetuses when intrauterine growth retardation is associated with microcephaly, arthrogryposis and ocular anomalies. Further studies are needed to better understand XPG functions during human development.